Design and Development of Small-Scale Oil Palm Waste Shredder for Achieving Environmental Sustainability - Lee, Mandjun; Lee, P. S. (Engineering Science Reference, 2020)
This chapter presents the design and development of an economically and technically feasible small-scale oil palm waste shredder to contribuite to oil palm waste management. Most available oil palm waste shredders are unaffordable due to high initial investment cost, large, heavy and unportable, which have been the drawbacks for small and medium enterprises to participate in the industry that relates with oil palm waste management. To address this issue, a low-cost and small-scale oil palm waste shredder were designed and produced. The central design concept deduced is to compromise acceptable efficiency with an affordable price by integrating all mandatory components of oil palm waste shredder into a comparatively small and portable support structure. The innovations made in the design are size reduction and adoption of double-shafts cutters with seven jaws technology. Preliminary calculations supported the design. The cutting force produced is up to 19.45kN with safety factor of 4.5. This design can handle other oil palm wastes as oil palm frond is harder than other oil palm wastes.